Economic Growth in Mozambique? An Assessment - Pier Giorgio Ardeni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
In this paper we try to assess the nature, size and consistency of recent economic growth in Mozambique. We attempt to verify whether and to what extent this growth is unprecedented as has been claimed. We look at the available data to assess whether this growth is even across sectors and GDP components. Finally we try to assess whether by any indication we can say if observed growth is balanced and, if not, to what extent economic policy is actually responsible. We argue that economic growth in Mozambique still appears to be out of balance, weak, uneven, and unsustainable, calling for a re-orientation of economic policy able to guarantee a more balanced and even growth across the economy. We also argue that, as a stable and steady economic growth is not warranted, Government action should be inspired to broaden its sets of instruments and goals, and that international agencies and donors should help it adopt the consequent policies. The spiral of debt, aid and conditionality certainly cripples Mozambique's Government autonomy, but it is only by broadening its sets of instruments and goal that Mozambique's economy will embark on a sustainable growth path.
Keywords: 330